Blocking Adenosine/A2AR Pathway for Cancer Therapy - Jia LIU; Yuequan SHI; Xiaoyan LIU; Dongming ZHANG; Yu BAI; Yan XU; Mengzhao WANG (Chinese Journal of Lung Cancer, 2022)
Adenosine is a metabolite produced abundantly in the tumor microenvironment, dampening immune response in inflamed tissues via adenosine A2A receptor (A2AR) which is widely expressed on immune cells, inhibiting anti-tumor immune response accordingly. Therefore, blocking adenosine signaling pathway is of potential to promote anti-tumor immunity. This review briefly introduces adenosine signaling pathway, describes its role in regulating tumor immunity and highlights A2AR blockade in cancer therapy. Prospective anti-tumor activity of adenosine/A2AR inhibition has been revealed by preclinical data, and a number of clinical trials of A2AR antagonists are under way. Primary results from clinical trials suggest that A2AR antagonists are well tolerated in cancer patients and are effective both as monotherapy and in combination with other therapies. In the future, finding predictive biomarkers are critical to identify patients most likely to benefit from adenosine pathway blockade, and further researches are needed to rationally combine A2AR antagonists with other anti-tumor therapies.